Water Quality of Canal For Sustainable Aquaculture In Reclaimed Tidal Lowlands - Raudhatus Saadah; M. Rasyid Ridho; Momon Sodik (Program Pascasarjana Universitas Sriwijaya, 2019)
The reclaimed tidal lowlands in Banyuasin, South Sumatera, Indonesia were initiated by making water canals that separate some areas to be some land groups. Those water canals are used for some activities such as agricultural, plantation, housing and water source for the people activities. This research aimed to observe the eligibility of water canals for sustainable fish culture. The data analysis of water qualities included ammonia, phosphate, nitrate, TSS, DO, pH, temperature, EC, salinity, water depth, detergent, and organochlorines. Cluster Test was used to analyze the data to compare the water qualities among canal areas. The results showed that detergent concentration was quite low, ranged at 63,5-74,5 ppm. Organochlorine found were Dieldrin 0,0084 ppm, while Linden, Eldrin, Heptklor, DDT, and Endosulfan concentration were below 0,001 ppm. Cluster Test showed that water quality in the canal was still in good condition, and can be used to support fish culture.